Technological solutions for processing fatty waste from the fishing industry to minimize environmental impact - М. М. Mushtruk; V. І. Matseiko; R. V. Chuiuk; N. M. Mushtruk; V. M. Mykhalska; I. A. Kharsika; V. I. Melnyk; N. T. Tverezovska; І. А. Petrychenko; А. А. Golovatyuk (Regulatory Mechanisms in Biosystems, 2026)
This paper presents an analytical review of fat-containing waste from fish processing enterprises as a promising secondary raw material for producing high-value products and reducing environmental burden. The study covers the main sources of waste generation in the fishing industry, in particular heads, entrails, skin, bone residues, and fat fractions, which are characterized by lipid content of 8–30%, free fatty acids of 5–25%, and moisture of 40–75%. It was established that these wastes have significant resource potential for the production of diesel biofuel, feed products, fatty acids, and biologically active compounds, particularly ω-3 polyunsaturated fatty acids. The chemical composition of fat-containing waste was studied, and the main groups of impur i ties were identified, including phospholipids, protein components, water, mineral salts, and oxidation products that affect the efficiency of technological processing. A comparative analysis of technological processing methods was carried out, including thermal, chemical, biotechnological, and methods of intensification of technological processes (ultrasound, cavitation, vibromechanical effects). It was established that under optimal conditions (temperature 50–65 °C, alcohol: fat ratio 6:1–9:1, humidity < 0.5%), the yield of biodiesel can reach 90–96%, while the use of methods of intensification of technological processes increases the degree of fat extraction by 10–25%. Approaches to complex waste processing using anaerobic digestion have been standardized, enabling the production of biogas with 55–70% methane content, as well as feed and protein products. A critical analysis of international and Ukrainian experience has been conducted, showing that waste utilization in EU countries reaches 90–98%, while in Ukraine it is 50–60%, indicating a significant reserve for increasing efficiency. The environmental assessment confirmed that implementing processing technologies can reduce greenhouse gas emissions by 60–85% and significantly reduce the volume of organic waste. The practical significance of the study lies in substantiating the selection of optimal technological solutions for processing fatty waste from the fishing industry, thereby increasing production resource efficiency, reducing env i ronmental load, and advancing bioenergy technologies in Ukraine.